Oxygen-vacancy mediated acidity and redox properties on WOx/Cu-doped CeO2 for the removal of NOx. Issue 5 (October 2021) - Hao, Zhifei; Liu, Guoquan; Ma, Nan; Zhang, He; Li, Yi; Xia, Yuguo; Zhang, Dongpeng; Zhan, Sihui
Abstract: Acidity and redox properties of the catalyst are two crucial factors affecting the performance of NH3 -SCR. Herein, we design a novel WOx /Cu-CeO2 oxide catalyst in which the WOx species are highly dispersed on the 111/100-terminated surface of Cu-doped CeO2 nanospheres, which exhibits great deNOx activity advantage and wide operating temperature window (200–400 °C, over 85% NOx conversion with a gas hourly space velocity (GHSV) of 60, 000 h −1 ), as well as good sulfur resistance and N2 selectivity. The relationship among the composition, acidity and redox properties of the WOx /Cu-CeO2 catalyst is established in the NH3 -SCR reaction. The combined experimental studies and spectroscopic characterization reveal that the introduction of Cu into the lattice of CeO2 not only increases the surface Ce 3+ and oxygen vacancy concentration but also provides more sites for capture and dispersion of WOx species, thus mediating and improving the Lewis and Brønsted acid sites and reducibility of catalyst. XPS and DFT calculations further demonstrate that electronic interaction between WOx and Cu-doped CeO2 is enhanced duo to the existence of interactions of short-range Ce-O-Cu and Ce-O-W. Moreover, the NH3 -SCR reaction over WOx /Cu-CeO2 may follow both Langmuir-Hinshelwood and Eley-Rideal reaction pathway according to the in situ DRIFTS. Graphical Abstract: ga1 Highlights: The addition of Cu and W significantly increased the NO conversion of CeO2 . Cu doping CeO2 increased the Ce 3+, O vacancy and enhanced the Lewis acid site. WOx improved Brønsted acidity and facilitated Langmuir-Hinshelwood mechanism. Existence of strong electronic interaction between WOx species and Cu-CeO2 .